Lip muscle training improves obstructive sleep apnea and objective sleep: a case report - Hiroshi Suzuki; Mayuko Yoshimiura; Yoshihiro Iwata; Sumito Oguchi; Misao Kawara; Chin-Moi Chow (Sleep Science)
The present study assessed the potential of lip muscle training for improving sleep. A patient with heavy snoring, daytime sleepiness and dry mouth underwent lip muscle training. Lip closure force LCFmax increased by 67.3% and LCFmin by 152% post-training. AHI decreased from 12.2 to 3.9 events/h by reducing hypopneic episodes. TST, sleep stage N3 and REM sleep increased, and WASO, sleep stage N1, and AI decreased. The patient switched from mouth to nose breathing during sleep and stopped snoring. Improved LCF, by moving the tongue into the anterior-superior oral cavity, may increase upper airway space and reduce the hypopnea index.